Riparian vegetation in production forest at Cemoro-Modang river, Cepu, Central Java - Agung Wahyu Nugroho; Heru Dwi Riyanto (Jurnal Penelitian Kehutanan Wallacea, 2018)
Production forest management is aimed at achieving not only economic benefit, but also environmental and social benefit. Riparian vegetation supports the improvement of environmental protection functions in the production forests. Riparian vegetation offers a number of environmental benefits related to water quality, streambank stabilization, and habitat. The study aims to study the potency of riparian vegetation (i.e. species composition, diversity, and similarity of species composition) in Cemoro and Modang river. This research was conducted in the forest for special purposes of Cemoro-Modang, Blora Regency, Central Java Province at BKPH Pasarsore and BKPH Cabak, KPH Cepu, Perum Perhutani Unit I. The inventory of riparian vegetation was conducted by making transects along the river sides combined with sample plots sized 20 mx20 m for trees, 10 mx10 m for poles, 5 mx5 m for saplings, 2 mx2 m for seedlings and 1 mx1 m for understory. The data collected were analyzed by vegetation analysis: Importance Value Index (IVI), species diversity, and similarity index. The result of the study showed that there are 114 species in the riparian zone of Cemoro[1]Modang river. There are 6, 2, 20, 16, and 85 species of vegetation for trees, poles, saplings, seedlings and understory vegetation, respectively. Riparian vegetation was dominated by Tectona grandis. Species diversity index for trees and poles were low, saplings and seedlings were moderate and understory was high. Similarity index between Cemoro and Modang river was low (i.e. 40.4%).